Picturing the Arctic. (1st October 2016) - Fjellestad, Marthe T.
ABSTRACT: Through a discussion of recent and historic photographs with origins in science, this paper explores how changing views of the Arctic coupled with new technology influence the pictures we as audiences outside the region are exposed to – and thus also our mental images of the region, our imaginary Arctic. An important feature of the Arctic as a modern cultural formation is the increased awareness of and interest in the polar area as a vital site for climate research and as a diverse region in the midst of rapid change. This is reflected through current practices of wide dissemination of research-related Arctic imagery in various news forum and social media aimed at general audiences. Through a study of two aerial photography surveys from Greenland, this paper demonstrates that as our thoughts on and about the Arctic continue to embrace new ideas and concepts, our image of what the region looks like expands, making room for diverse and sometimes disparate views.